Is universal child care leveling the playing field? - Tarjei Havnes; Magne Mogstad (University of Oslo, Department of Economics, 2012)
Many developed countries currently consider a move towards a universal child care program. The challenge in assessing the case for universal child care programs is that the evidence base is scarce. We analyze the staged expansion of subsidized, universally accessible child care in Norway. Our approach differs from existing literature which estimate mean impacts of universal child care programs; in contrast, we use non-linear difference-in-differences methods to estimate quantile treatment effects, showing how the child care expansion affected the earnings distribution of exposed children as adults. We complement these estimates with local linear regressions of the child care effects by family income. Our findings suggest that the effects of child care vary systematically across the earnings distribution, that the mean impact misses a lot, and that children of low income parents seem to be the primary beneficiaries of subsidized child care. These findings are important when considering the case for universal child care programs, since the benefits of providing subsidized child care to middle and upper-class children are unlikely to exceed the costs. To help understand the differential effects on earnings, we examine how the child care expansion affected the educational trajectories and cognitive test scores of the exposed children.
Keywords: J13; H40; I28; D31; 330; universal child care; child development; non-linear difference-in-differences; heterogeneity; quantile treatment effects; Kinderbetreuung; Familienpolitik; Bildungsertrag; Verteilungswirkung; Nichtlineares Verfahren; Statistischer Test; Norwegen